Faktor-Faktor yang Memengaruhi Minat Penggunaan Financial Technology Payment pada UMKM di Kota Batam - Tri Purwanti; Argo Putra Prima (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The development of financial technology (fintech), particularly in digital payment systems, offers significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to improve the efficiency and effectiveness of financial transactions. However, interest in using fintech payments among MSMEs is still influenced by various factors. This study aims to analyze the influence of perceived ease of use, accountability, transparency, and trust on interest in using financial technology payments among MSMEs in Batam City. This study used a quantitative approach with primary data obtained through questionnaires distributed to 96 MSMEs selected using a purposive sampling technique. Data analysis methods used included descriptive statistical tests, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis tests, and coefficient of determination tests using SPSS version 27. The results showed that partially perceived ease of use, accountability, transparency, and trust had a positive and significant effect on interest in using financial technology payments. Furthermore, the results of the simultaneous test showed that all independent variables together had a significant effect on interest in using fintech payments. This study concludes that increasing convenience, accountability, transparency, and trust can encourage the adoption of fintech payments in MSMEs.